TYPICAL WEDDING TUNES OF THE NORTHERN-MEZŐSÉG (CÂMPIA TRANSILVANIEI)* - Zoltán GERGELY (Studia Universitatis Babeş-Bolyai. Musica)
The typical events of a wedding in the Northern-Mezőség are mainly the same as those of the weddings of all the Hungarian population. During each event of the wedding the lyrics of the songs sung during the event express the function of that event. The collection of songs typically sung at the wedding differs from one smaller geographical unit of the Mezőség to the other, sometimes even from village to village. The greatest collection of songs belongs to the village of Szék (Sic). Some of these songs can be found also in the collection of wedding songs of the Romanian population living in the village. Since there has been a collection of data in the course of the last half century, the processing of these data makes it possible to form – parallel to the collection of songs – a reconstructed image of the traditional typical events and customs of the weddings of Mezőség, greatly altered by our days.